2017
DOI: 10.3892/ol.2017.5815
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SPG20 gene promoter-methylated DNA, as a novel epigenetic biomarker, in plasma for colorectal cancer diagnosis using the MethyLight method

Abstract: Abstract. Aberrant promoter methylation of genes is a common epigenetic alteration in colorectal cancer (CRC). In the present study, spastic paraplegia 20 (SPG20) promoter-methylated DNA, as a potential diagnostic biomarker, was investigated in plasma and tumor tissue samples from patients with CRC. To the best of our knowledge, the quantification of SPG20 promoter-methylated DNA in plasma samples remains unreported. SPG20 promoter methylation was investigated in 32 paired tumor and healthy adjacent tissues, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The SPG20 gene encodes a protein called Spartin that has been found to be involved in intracellular epidermal growth factor receptor trafficking; SPG20 promoter has been found to be hypermethylated in colorectal cancer, resulting in gene silencing and cytokinesis arrest [ 40 ]. SPG20 promoter hypermethylation was also validated as a novel noninvasive biomarker [ 41 ]. MCM2 is one of six highly conserved proteins recruited to form the MCM protein complex, a cell ubiquitous hexamer that works as molecular motor performing DNA duplex unwinding and fork progression during DNA replication [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The SPG20 gene encodes a protein called Spartin that has been found to be involved in intracellular epidermal growth factor receptor trafficking; SPG20 promoter has been found to be hypermethylated in colorectal cancer, resulting in gene silencing and cytokinesis arrest [ 40 ]. SPG20 promoter hypermethylation was also validated as a novel noninvasive biomarker [ 41 ]. MCM2 is one of six highly conserved proteins recruited to form the MCM protein complex, a cell ubiquitous hexamer that works as molecular motor performing DNA duplex unwinding and fork progression during DNA replication [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present systematic review, we identified two studies investigating this biomarker in more than one type of material, although none of these studies included adenomas. Rezvani et al found methylated SPG20 in 94% of CRC tissues and correspondingly in 81% of the plasma samples from these patients [ 41 ]. The specificity in tissue samples was 99% and in plasma samples 97% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rezvani et al found methylated SPG20 in 94% of CRC tissues and correspondingly in 81% of the plasma samples from these patients [ 41 ]. The specificity in tissue samples was 99% and in plasma samples 97% [ 41 ]. Zhang et al found methylated SPG20 in 85% of CRC tissues and correspondingly in 80% of stool samples from these patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other two approaches for MSP quantification included two control PCR products: ALU–C4 ( ALU ) as a DNA input normalizer and commercial methylated bisulfite-converted human DNA (Qiagen) as a fully methylated control [32,33]. Equations used for these two approaches were:PMR= M/U / ALU for sample M/U / ALU for methylated control and PMR= M / ALU for sample M/ ALU for methylated control where in all three approaches for the quantification of MSP: PMR > 1 indicates a strong MGMT promoter methylation (hypermethylated), PMR = 0 (no M primer MSP product detectable) indicates an unmethylated MGMT promoter and PMR < 1 indicates weak MGMT promoter methylation.…”
Section: Methodsmentioning
confidence: 99%